“ANTROPOMAQUIA” OU ACERCA DO PODER, O VENENO QUE O CORAÇÃO NÃO CALA - FERREIRA, Kevin de Abreu (2023)
This interdisciplinary dissertation covers the processes of research, writing and general elaboration of the course conclusion work intended for the academic and interdisciplinary master's degree in the Postgraduate Program in Culture and Society (PGCult), contemplating the research line "Expressions and sociocultural processes". Its object of study is a possible continuity between the concept of “Care of the Self”, by Michel Foucault; and the process of “Escrevivência” (“Selfwriting”), by Conceição Evaristo. It follows that, in A) carrying out a Cartography of the formative path of the concept of Care of the Self, B) an Archeology of the Escrevivência & C) a Genealogy of the (Un)Colonial Power, we sought the discursive elaboration of a “Policy of Health” and a “History of Truth” – considering the Care for the Self as a starting point to consider the Escrevivência, or Double-Faced Writing, as an experience of health and a cultivation of well-being, on one side; and, on the other, as a critical experience of insubmission expressed through a Decolonial position, in Evaristo's Work and Thought. Our starting point, an interdisciplinary investigation and writing - between literature, philosophy and psychology - of the Works of Conceição Evaristo and Michel Foucault, begins with a fundamental question: to what extent is it possible to interpret the concept and praxis of Escrevivência, by Conceição Evaristo, as an experience of Care of the Self, as understood from the thinking of Michel Foucault? This dissertation is an invitation for a methodological, conceptual and documentary paths based on the textual analyzes of both authors, philosophicaly and treatise-like.